Learning, making and flourishing in non-formal spaces: Participatory arts and social justice. (March 2022) - Wright, Peter; Down, Barry; Davies, Christina
This article considers Participatory Arts and sociocultural understandings of justice and praxis through the example of Big h ART, an Australian multi-award winning provider where both artists and participants – often disenfranchised and marginalised young people – co-create the work (Matarasso, 2018). Enacting social justice principles, Big h ART works alongside young people to improve their life outcomes through arts practice strengthening young people's critical capabilities by inducting them as both makers and responders to their own lives and the world around them. Drawing on three years of ethnographic research across three sites in rural and regional Australia we highlight how multidimensional and multi-modal arts-based projects contribute to young people's lives through theorising the attributes and dimensions of twenty productive conditions and practices identified as essential for social change. These possibilities are important as when these conditions are purposefully enacted, the power of the arts for sense-making and identity development is revealed in non-formal learning spaces. Theoretically unpacking these conditions and practices and linking them with research outcomes helps build understanding of the generative power of Participatory Arts through the ways Big h ART builds bridges between young people and their communities and the developmental trajectories they may take through being 'at-promise' rather than 'at-risk'.